Extração de Al(III), Cr(III) e Fe(III) de meio etanólico usando o xerogel anilinapropilsílica - Pavan Flávio A.; Costa Tania M. H.; Benvenutti Edilson V.; Jacques Rosângela A.; Córdova Manuela C. (Química Nova, 2004)
In this study, the preparation of the xerogel anilinepropylsilica is reported. The ability of the xerogel for extracting Al(III), Cr(III) and Fe(III) from ethanol was investigated at 25 ºC. The xerogel adsorption capacities were obtained from the adsorption isotherms by using the batch method. Flame atomic absorption spectrometry (FAAS) was used to estimate the concentration of metal ions in solution. The adsorption affinity follows the series Cr(III) > Fe(III) > Al(III) and the maximum adsorption capacities of the metal ions were 0.61, 0.52 and 0.43 mmol g-1, respectively.